Digital transformation in public service: Evaluating e-government implementation and fiscal performance at Samsat Pajajaran Bandung - Fritiar, Inkha Hedian Dena (Privietlab, 2026)
This study evaluates the implementation of e-government policies at Samsat Pajajaran, Bandung, focusing on fiscal performance and operational efficiency. Employing a qualitative case study design, data were gathered through in-depth interviews with purposively selected informants, including operational officers and taxpayers, as well as field observations and fiscal report analysis. The findings demonstrate that digitalization via the SIGNAL and e-Samsat platforms has successfully catalyzed local genuine revenue (PAD) growth, with a projected increase of IDR 250 billion by 2025. Operationally, service efficiency improved by 66.7%, reducing processing time from 45 to 15 minutes. However, the study identifies a significant digital divide affecting elderly taxpayers and technical latencies during peak hours. This research recommends a 50% increase in API server capacity to ensure socially inclusive governance.